STUDI PEMANFAATAN FASILITAS TEMPAT PELELANGAN IKAN DI PELABUHAN PERIKANAN NUSANTARA PEKALONGAN PROVINSI JAWA TENGAH - Siburian, Ardi A.; Syaifuddin, Syaifuddin; Rengi, Pareng (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACK                Pekalongan Fish Auction Place has adequate equipments and facilities, but the auction activity for the catch above eighty tons can not be done in one auction. The problems that arise are the existence of facilities and equipments in TPI that are not used optimally, in addition there are some regulations in the fishing port that has not been fully implemented, especially landing activities and port securities. The purpose of this study is to determine the level of utilization of facilities and equipments and constraints that exist in the TPI. The benefit of this study is as a consideration in taking policy regarding the level of utilization of facilities and equipment TPI. Thus the research needs to be done related to the study of the utilization of facilities and equipment TPI Research conducted at Fishery Port of Nusantara Pekalongan, on 19th-26th October 2017. The method used in this research is survey method. By collecting data as much as possible about TPI facilities and equipments that support the auction activity. The facilities in TPN PPN Pekalongan are TPI office and TPI building and equipments in TPI are baskets, auctioneer seats, carts, sorong, scales, loudspeakers and lamps. After analyzed, the results obtained are equipments and facilities utilized/optimized about 80.01-100% (very good) which is slide and loudspeakers, while equipments and facilities in the utilization process about 40,01-60% (medium) that is building, chair of auctioneers and scales. Further equipments and facilities utilized/optimimized about 0-40% (very less good) which is TPI lamps, baskets, and carts. Keywords: Fish auction place, PPN Pekalongan, Facilities and equipment, Utilization